Tracking Government Responses to Covid-19: The CoronaNet Research Project - Cindy Cheng; Luca Messerschmidt; Svanhildur Thorvaldsdottir; Clara Albrecht; Christa Hainz; Tanja Stitteneder; Joan Barceló; Vanja Grujic; Spencer Hartnett Allison; Robert Kubinec; Timothy Model; Caress Schenk (CESifo Forum, 2021)
Governments around the world have taken a significant number and variety of actions in response to the Covid-19 pandemic. To understand this flood of government actions, policymakers and researchers need access not only to high-quality, up-to-date data on government responses, but also tools to help them make sense of that data. In a joint initiative, the data collected in CoronaNet are visualized on the ifo Institute's DICE website. The following article introduces the CoronaNet research project and explains some of the data collected and how they are presented on DICE.
Keywords: 330